Comparison of the modified piggyback with standard piggyback and conventional orthotopic liver transplantation techniques: a network meta-analysis - Khajeh, Elias; Ramouz, Ali; Aminizadeh, Ehsan; Sabetkish, Nastaran; Golriz, Mohammad; Mehrabi, Arianeb; Fonouni, Hamidreza (HPB, 2023)
Background - In conventional orthotopic liver transplantation (OLT), the recipient's retrohepatic inferior vena cava (IVC) is completely clamped and replaced with the donor IVC. The piggyback technique has been used to preserve venous return, either via an end-to-side or standard piggyback (SPB), or via a side-to-side or modified piggyback (MPB) anastomosis, using a venous cuff from the recipient hepatic veins with partially clamping and preserves the recipient's inferior vena cava. However, whether these piggyback techniques improve the efficacy of OLT is unclear. To address the low quality of the available evidence, we performed a meta-analysis to compare the efficacy of conventional, MPB, and SPB techniques. - Methods - Literature was searched in Medline and Web of Science databases for relevant articles published until 2021 without any time restriction. A Bayesian network meta-analysis was performed to compare the intra- and postoperative outcomes of conventional OLT, MPB, and SPB techniques. - Results - Forty studies were included, comprising 10,238 patients. MPB and SPB had significantly shorter operation times and fewer transfusions of red blood cell and fresh frozen plasma than conventional techniques. However, there were no differences between MPB and SPB in operation time and blood product transfusion. There were also no differences in primary non-function, retransplantation, portal vein thrombosis, acute kidney injury, renal dysfunction, venous outflow complications, length of hospital and intensive care unit stay, 90-day mortality rate, and graft survival between the three techniques. - Conclusion - MBP and SBP techniques reduce the operation time and need for blood transfusion compared with conventional OLT, but postoperative outcomes are similar. This indicates that all techniques can be implemented based on the experience and policy of the transplant center.